Schematic Representation of Lexical Meaning: A Cognitive Linguistic Study of Selected Entries from Lisan al-Arab - Al-Hogbani, Abdullah bin Saad bin Faris (Arts for Linguistic & Literary Studies, 2025)
This study, grounded in cognitive semantics, explores how mind maps can be applied to lexicography in order to uncover the conceptual and mental structures underlying meaning. Focusing on selected entries from Ibn Manzur’s Lisan al-Arab, particularly verbs of motion and nouns referring to body parts, the research moves from a theoretical discussion of mind maps to a practical analysis of their application. The study extracts core meanings, organizes them schematically, and reveals the conceptual frameworks shaping them. The findings demonstrate that semantic expansion does not occur through arbitrary convention but evolves via interrelated categories that branch from an original core meaning into derived sub-meanings. Such expansions are made possible by conceptual relations linking primary and secondary senses, which in turn allow meaning to be systematically structured and schematically represented. The results highlight the value of cognitive approaches in rethinking lexical semantics, positioning language as a mental activity grounded in perception, embodiment, and experience.